Assessment of static and perfusion methods for decellularization of PCL membrane-supported periodontal ligament cell sheet constructs. (April 2018) - Farag, Amro; Hashimi, Saeed M.; Vaquette, Cedryck; Volpato, Fabio Z.; Hutmacher, Dietmar W.; Ivanovski, Saso
Highlights: Cell sheets constructs were prepared using human PDL placed onto PCL membranes. Constructs were decellularized under static/perfusion conditions. Collagen and growth factors quantification, immunostaining and SEM were performed. No significant differences between different decellularization methods in DNA removal after DNase treatment. NH4OH/Triton X-100 and DNase solution was the most efficient method. Abstract: Objectives: Decellularization aims to harness the regenerative properties of native extracellular matrix. The objective of this study was to evaluate different methods of decellularization of periodontal ligament cell sheets whilst maintaining their structural and biological integrity. Design: Human periodontal ligament cell sheets were placed onto melt electrospun polycaprolactone (PCL) membranes that reinforced the cell sheets during the various decellularization protocols. These cell sheet constructs (CSCs) were decellularized under static/perfusion conditions using a) 20 mM ammonium hydroxide (NH4OH)/Triton X-100, 0.5% v/v; and b) sodium dodecyl sulfate (SDS, 0.2% v/v), both +/− DNase besides Freeze–thaw (F/T) cycling method. CSCs were assessed using a collagen quantification assay, immunostaining and scanning electron microscopy. Residual fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF) and hepatocyte growth factor (HGF) were assessed with Bio-plex assays. Results: DNA removal without DNase was higher under static conditions. However, after DNase treatment, there were no differences between the different decellularization methods with virtually 100% DNA removal. DNA elimination in F/T was less efficient even after DNase treatment. Collagen content was preserved with all techniques, except with SDS treatment. Structural integrity was preserved after NH4OH/Triton X-100 and F/T treatment, while SDS altered the extracellular matrix structure. Growth factor amounts were reduced after decellularization with all methods, with the greatest reduction (to virtually undetectable amounts) following SDS treatment, while NH4OH/Triton X-100 and DNase treatment resulted in approximately 10% retention. Conclusions: This study showed that treatment with NH4OH/Triton X-100 and DNase solution was the most efficient method for DNA removal and the preservation of extracellular matrix integrity and growth factors retention.